Predictive validity of the dynamic risk assessment and management system in individuals with intellectual disability residing in the community - Lindsay, William R. (Psychology, crime & law, 2018)
Background. The Dynamic Risk Assessment and Management System (DRAMS) was created to measure dynamic risk in individuals with intellectual disabilities (ID). Steptoe, Lindsay, Murphy, and Young, (2008) examined the construct validity, reliability and predictive validity of the dynamic risk assessment and management system (DRAMS) in offenders with intellectual disability and found that the total DRAMS score and sections on mood, antisocial behaviour and intolerance/agreeableness predicted incidents with a medium effect size for offenders with ID residing in high secure settings.